IPTEKS PROSEDUR PENILAIAN ASET TETAP PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG (KPKNL) MANADO - Maruf, Juniarti Melisa; Tampang, Elisabeth; Walandouw, Stanley Kho (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Fixed assets are tangible assets to be owned or used in the production, supply of goods or services. Aim to administer and be used for more than one period. In this material there is a procedure where as a stage of activity activities to solve it and steps to resolve a problem. Assessment is the process of activities to provide value opinions on objects of valuation in the form of State Property. Fixed Assets consist of two types, namely tangible fixed assets and intangible fixed assets. The purpose of this study was to analyze the procedure for assessing fixed assets at KPKNL Manado. The method used is an analysis of the valuation of the fixed assets of KPKNL Manado. The results of the study are in accordance with the existing reports, still collecting some background information, clear requests, objectives for assessment and description of the object of assessment.Keywrods: Procedure, Assessment, Fixed Assets